“No miracle cure” interface evaluation of a UK suicide prevention app in a Norwegian context - Kari Dakota Aasheim; Thea Heggeli Bråthen; Kristine Brandager Reiersen; Mimi Alexandra Erichsen; Kristina Sande Storevik; Anne Lund (Scandinavian Journal of Occupational Therapy)
Background 600 Norwegians die by suicide annually. Self-help apps may potentially reach and support suicidal individuals, next of kin, bereaved and professionals with educational information, access to suicide emergency help, hotlines, and coping tools. Knowledge regarding feasible app interface for suicide prevention self-help apps in a Norwegian context is however lacking.Aim Evaluate user-friendliness and user interface of the Norwegian version of the British Stay Alive suicide prevention app and assess whether the app could be useful in suicide prevention.Materials and Methods Eight Norwegian Fountain house members and twelve university students evaluated the app interface, and their experiences were discussed through individual- or focus-group interviews.Results Participants perceived app tools as relevant and useful for suicide prevention, however they raised concerns on privacy, evidence base, interface complexity, unintended symbolic value of app colours and content, and suitability in suicidal states.Conclusion The current Norwegian Stay Alive version has the potential to be user friendly, however improvements of interface are suggested.Significance Stay Alive interface must be adjusted and subjected to reiterative evaluations and feasibility assessments in collaboration with additional stakeholder populations to remedy interface concerns, and identify optimal Norwegian interface design, prior to implementation.